Lessons learned from functional assessment of pluripotency-associated transcription factors during early embryogenesis and embryonic stem cells - da Silva, Priscila Germany Corrêa; Tigre Moura, Marcelo; Cantanhêde, Ludymila Furtado; Ferreira-Silva, José Carlos; Nascimento, Pábola Santos; Silva, Roberta Lane de Oliveira; dos Santos Filho, José Pompeu; Lemos Oliveira, Marcos Antonio (Medicina Veterinária, 2017)
Pluripotency-associated transcription factors (PATF) play significant roles during early embryogenesis and in embryonic stem (ES) cells, such as control of cell-cycle progression, modulation of cellular metabolism, and transcriptional control of differentiation-inducing factors. The review aims to describe the current understanding of how these PATFs contribute to the early embryo and the ES-cell phenotypes. By a selection of representative examples of such PATFs, their roles are described, and some interesting questions are presented concerning their activity in pluripotent cells which have yet to be addressed.